Bilious pleural effusion: A rare complication of acute cholangitis following percutaneous transhepatic biliary drainage–A case report - Cheng-Wei Yang; Pi-Teh Huang (Tungs’ Medical Journal, 2025)
Bilious pleural effusion (cholethorax or bilothorax) is an uncommon presentation as a complication induced by the gallbladder and biliary tree interventions. Fistula formation between the pleural space and biliary tree has been documented following percutaneous transhepatic gallbladder drainage, percutaneous transhepatic cholangio drainage (PTCD), and endoscopic retrograde cholangiopancreatography, typically occurring when the catheter passes through the pleural space before reaching the intended location. Thoracentesis is essential for diagnosing bilious pleural effusion, confirmed by pleural effusion color and pleural/serum bilirubin ratio analysis. Here, we present a case of an 80-year-old female with obstructive cholangitis with a common bile duct stone, and bilious pleural effusion was observed following PTCD with a developing right lung empyema. Conservative pleural drainage along with endoscopic sphincterotomy was performed.